Aylluy and sustainable trans-complex simplicity: a transdisciplinary research model: a transdisciplinary research model - Domínguez Condezo, Víctor (2020)
The natural world was always considered a model of connective, coherent, and projective knowledge. Did the specialization fragmented and disarticulated this harmonic and integral structure? Currently, while facing a world that has become so complex, this specialization reformulates its analysis, reconstructs and reinterprets our problems, to rethink a systematic and restructured world through complex thinking and transdisciplinary solutions. This article evaluates particularity in university research, and reconsiders interdisciplinary, trans-complex and transdisciplinary teamwork, from connective and integral Andean thinking based on the nuclear and harmonic organization between nature, man and society. From this Andean framework, we recover the «aylluy» thought (trans-complex simplicity, unity, and sustainability) as a research model for the educational process and the environment. For this research, we applied qualitative, descriptive, and analytical methodology.